2021
DOI: 10.1002/slct.202103675
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis of Polysubstituted Coumarin‐pyrrolo[2,1‐a]isoquinoline‐1‐carbaldehydes from Isoquinoline, 2‐Bromoacetophenones and Coumarin‐β‐chlorovinyl Aldehydes

Abstract: In this research, a simple and efficient strategy for the straightforward synthesis of polysubstituted coumarin‐pyrrolo[2,1‐a]isoquinoline‐1‐carbaldehydes is presented by a sequential three‐component reaction of isoquinoline, 2‐bromoacetophenones and 3‐chloro‐3‐(2‐oxo‐2H‐chromen‐3‐yl)acrylaldehydes as readily available starting materials, which includes base‐mediated 1,4‐addition or [3+2] cycloaddition/intramolecular cyclization/formation two C−C bonds/aromatization tandem reaction under air. In this method, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Alizadeh et al reported a three-component synthesis of coumarin based pyrrolo[2,1- a ]isoquinoline carbaldehyde 199 (Scheme 39). 83 Isoquinoline 195 reacts with 2-bromoacetophenone 196 to form isoquinolinium ylide 197 . The reaction of 197 with aldehyde 198 through [3 + 2] cycloaddition or nucleophilic conjugate addition of ylide 197 to acrylaldehyde 198 , followed by intramolecular cyclization, affords isoquinoline scaffold 199 .…”
Section: Catalyst-free Protocolsmentioning
confidence: 99%
“…Alizadeh et al reported a three-component synthesis of coumarin based pyrrolo[2,1- a ]isoquinoline carbaldehyde 199 (Scheme 39). 83 Isoquinoline 195 reacts with 2-bromoacetophenone 196 to form isoquinolinium ylide 197 . The reaction of 197 with aldehyde 198 through [3 + 2] cycloaddition or nucleophilic conjugate addition of ylide 197 to acrylaldehyde 198 , followed by intramolecular cyclization, affords isoquinoline scaffold 199 .…”
Section: Catalyst-free Protocolsmentioning
confidence: 99%
“…Alizadeh and Rostampoor 71 disclosed a one-pot metal-free, green synthetic strategy for the synthesis of polysubstituted coumarin-pyrrolo[2,1- a ]isoquinoline-1-carbaldehydes instead of lamellarin derivatives through sequential three-component reaction of isoquinoline, 2-bromoacetophenones and 3-chloro-3-(coumarin-3-yl)acrylaldehydes via chemoselective [3+2] cycloaddition/intramolecular cyclization and aromatization in the presence of triethylamine in acetonitrile solvent at room temperature under air (Scheme 13).…”
Section: Introductionmentioning
confidence: 99%
“…1 a – i As such, there is growing demand to develop efficient methods for straightforward construction of the pyrrolo[2,1- a ]isoquinoline scaffold. 2–6 Conventional methodologies generally involve two different modes of reactivity as the final step, including construction of a pyrrole framework on the existing isoquinoline ring 2–5 or assembly of an isoquinoline unit on the existing pyrrole ring. 6 Typically, approaches for construction of a pyrrole framework on the existing isoquinoline ring have been proven to be powerful and popular, and are focused on cycloaddition reactions with activated unsaturated hydrocarbons (such as alkynes, alkenes and allenes), including 1,3-dipolar cycloaddition reactions, electrocyclization, Michael/condensation reactions, Michael/substitution reactions, Michael/oxidative C–N coupling reactions and N -ylide-based annulation reactions.…”
mentioning
confidence: 99%
“…6 Typically, approaches for construction of a pyrrole framework on the existing isoquinoline ring have been proven to be powerful and popular, and are focused on cycloaddition reactions with activated unsaturated hydrocarbons (such as alkynes, alkenes and allenes), including 1,3-dipolar cycloaddition reactions, electrocyclization, Michael/condensation reactions, Michael/substitution reactions, Michael/oxidative C–N coupling reactions and N -ylide-based annulation reactions. 2–5 These cycloaddition transformations often first require the conversion of isoquinolines and their derivatives into highly reactive isoquinolinium salts (ylides), 3,4 which thus enable cycloaddition with the activated unsaturated hydrocarbons to assemble pyrrolo[2,1- a ]isoquinoline frameworks. Despite these advances, such methods, and more specifically the methods that consist of an intermolecular annulation of isoquinolinium salts (ylides) with alkynes, remain underdeveloped.…”
mentioning
confidence: 99%